In-Hospital Outcome of Compromised Small Side Branch after Percutaneous Coronary Intervention (Cardiovascular Journal, 2014)
Background: Side branch occlusion is a well known complication of percutaneous coronary intervention. Although occlusion of small side branches is well tolerated, occlusion of larger side branches may cause more serious complications. After PCI the incidence of complications in patients with compromised side branches smaller than 2 mm is small. Compromising side branches larger than 2 mm can be accompanied by clinical outcomes as non Q-wave MI. This study was undertaken to assess the in-hospital outcomes of compromised small (